Power Dynamics of India's Space Program. Issue 2 (1st September 2016) - Lele, Ajey
ABSTRACT: Space power is a relatively nascent discourse that is gaining importance globally. This article examines India's space program within the global context in order to understand the shifting power balance in the space arena. The article first clarifies contextual variants of the definition of power, recalibrating those formulations to the space context. This is followed by an examination of the Indian space program—its evolution historically, current limitations, and increasing relevance today. Space is a versatile domain and, due to its interconnected nature, it impacts the world. Hence, this article also examines global engagements and collaborative efforts being made across borders, and the strategic modalities involved in traversing such sensitive diplomatic terrain. Finally, the article concludes by reiterating the soft power and hard power potentials of the space arena, whose versatility contributes towards intrinsic national growth and extrinsic power projections.